What kind of God? : collected essays of Terence E. Fretheim - Fretheim, Terence E. (Siphrut, 2015)
"The goal of the collection is to present in curated form a selection of writings that highlight Fretheim's most significant and enduring insights. To this end, the 32 pieces included here are organized into thematic subsections that are meant to capture major themes in Fretheim's work. The volume begins with 2 essays situating Fretheim and his work--one by the editors and one by Fretheim himself (part 1). The essays in part 2, "God and the World," deal with Fretheim's understanding of God and God's relationship to the created order. Part 3, "God and Suffering," features pieces on the suffering of God and the world and includes an excerpt from Fretheim's groundbreaking book The Suffering of God. Part 4 is titled "God and Wrath." The essays gathered here deal with three overlapping themes: the wrath of God, divine violence, and God's frequent association with violence in the Old Testament. Part 5, "God and the Pentateuch," contains 6 essays that focus especially on Genesis 1-11, Exodus, and Deuteronomy. The essays in part 6 on "God and the Prophets" deal with various theological themes in the former, major, and minor prophets--all marked by Fretheim's unmistakable style and approach. The last part of the collection, part 7, "God and the Church's Book," address specific issues related to Christian theology, with an eye on denominational and congregational contexts. The volume concludes with a bibliography of Fretheim's works (1969-2013)"--